Linguistic politeness of the world strategies used by organizers of youth international conferences in writing rejection letters (2015)
The study explores the politeness strategies deployed in rejection letters from youth international conferences. It aims to identify the politeness marker(s) that characterize a specific politeness strategy. Furthermore, this paper attempts to describe the general macrostructure of the said rejection letters by analyzing the strategic positioning of politeness strategies in these letters. Thirty (30) rejection letters written by organizers of youth international conferences served as the corpus of the study. By utilizing Brown and Levinson’s or B&L’s (1987) Politeness Theory Model and Baresova’s (2008) framework, the researchers examined these letters of rejection and identified the politeness strategies employed in writing them. The findings revealed that being optimistic and noticing or attending to the hearer are the two most commonly used politeness strategies in rejection letters from youth international conferences. These strategies are often marked by optimistic phrases (i.e., presuming an applicant’s willingness to cooperate and a positive outcome), and thank-you phrases (i.e., expressing gratitude upon interest in the conference). Moreover, the results suggest that the general macrostructure of the rejection letters follows the proposed refusal sequence that includes (1) preparation for rejection, (2) actual rejection, and (3) remedy. This paper affirms the applicability of B&L’s politeness theory in writing rejection letters for youth international conferences, while also describing the linguistic features of politeness.
Keywords: Authorship; Politeness (Linguistics)